Estudio de factibilidad para la creación de una caja de ahorro y crédito en la florícola Flor Magic - Cartagena, Damaris A. (2023)
The objective of this research is to carry out a feasibility study for the creation of a savings bank in the florist FLORES MÁGICAS FLOR MAGIC CIA, LTDA located in the city of Cayambe. The main purpose is to determine the financial viability of this project, which aims to offer social and economic support to the florist's staff, based on real data and future projections.